IMPROVEMENT PRODUCTION LINE AND LINE BALANCING ON PROJECT AMAZON DD 400 G WITH USING VALUE STREAM MAPPING (STUDY CASE AT PT. XYZ) - Ardiyanto, Ardi; Pangestu, Audy Raka; Oktarina, Rienna; Aryanti, Jenny; Yansyah, Sendra Pebri; Gunawan, Fergyanto E. (INFOKUM, 2022)
PT. XYZ Manufactures and distributes electrical products. XYZ Company there are some issue in production Line, for the assembly process on High-speed cables consists of 3 lines, namely the Cutting line, Assembly Line and Measurement Test Line. Where the Assembly Line has a fairly long process compared to other lines, with the occurrence of line imbalances in production causing idle time on other lines and the buildup of WIP inventory on the cutting line because the information between the cutting line and the assembly line data is not updated automatically. The purpose of this study is to provide a reference for improvement methods in the production process, such as kaizen and line balancing in the Assembly process, by recalculating the determination of the number of operators in production, relocating the assembly line to the Cutting line and Measurement test line, and developing a traceability system that integrates with each line. Researchers use Value stream mapping to find out the waste that occurs and the operation process chart to find out which processes need improvement. The results of this study resulted in an optimal line balance method and the optimal number of operators used for the manufacture of High-speed Cables, which can reduce production cycle time to 90.98 minutes from the previous 115.01 minutes and operator requirements to 29 operators from the previous 40 operators.